(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The end of the 15th century, various fields of culture flourished in the Ottoman society. A number of talented poets such as poetess Mehri Khotun and poet Mulla Mahmud have grown up in the country. Turkish architecture grew using the experience of master-builders brought from different countries. The wonderful architectural masterpieces built by Khoja Sinon, who is a Greek, made him known to the whole world. During his career, he led the construction of more than 300 structures: mosques, madrasas, palaces, fountains, baths, and bridges. The development of geography among various fields of science is particularly noteworthy.